Analisis Pelaksanaan Penyusunan Administrasi Kepenghuluan di Kementerian Agama Kabupaten Ogan Ilir - Iswardi, Iswardi; Syuroh, Mat; Febrianza, Muhammad (@-Publik: Jurnal Administrasi Publik, 2024)
In the Regulation of the Director General of Islamic Guidance No. DJ.II/426 of 2008 concerning Guidelines for the Implementation of Duties and Credit Score Assessment for the Functional Position of "Penghulu" (Islamic marriage officiant), the main tasks of a Penghulu include planning community marriage-related activities, supervising the recording of marriages or divorces, conducting marriage or divorce services, providing advice and consultation on marriage and divorce, monitoring violations of marriage and divorce regulations, issuing legal opinions (fatwa) on marital matters, providing guidance in Islamic transactions (muamalah), and developing community marriage-related activities. In addition, their duties also encompass the development of harmonious families and monitoring and evaluating community marriage-related activities. The purpose of this research is to analyze the implementation of administrative processes related to the role of Penghulu in the Ministry of Religious Affairs in the Ogan Ilir Regency. Some of the identified issues include a lack of human resources to record marriage and divorce events using the SIMKAH WEB system, as well as deficiencies in infrastructure, particularly in terms of internet connectivity and computers. This research employs qualitative data analysis techniques, collecting data through interviews, documentation, and observation. The research findings indicate that, in general, the administrative processes related to the role of Penghulu in the Office of the Ministry of Religious Affairs in Ogan Ilir Regency are being carried out as expected. However, there are still challenges related to a shortage of human resources for recording marriage and divorce events using the SIMKAH WEB system, as well as deficiencies in infrastructure, particularly in terms of internet connectivity and computer resources.